Factors Influencing Job Satisfaction of Healthcare Workers at Bhayangkara Level III Hospital in Kendari City - Hana, Adelfina Maretti; Suhadi, Suhadi; Ruslan, Ruslan (PT. Riset Press International, 2024)
Job satisfaction is a subjective experience influenced by individual values and personal perspectives. The greater the alignment between a job and a person's aspirations, the more happiness they are likely to feel. This research aims to identify the factors influencing job satisfaction among healthcare workers at Bhayangkara Tk. III Hospital in Kendari City in 2024. A cross-sectional survey method will be employed, with the research conducted from January to February 2024. The study population consists of 204 people, with a sample size of 135 healthcare workers selected through purposive sampling. The criteria for participation are active employment and willingness to be respondents. Data will be analyzed using univariate, bivariate, and multivariate methods. The results indicate that salary and incentives significantly affect job satisfaction. The work environment, workload, leadership recognition, and work motivation also have significant impacts on job satisfaction. In conclusion, Bhayangkara Tk. III Hospital must improve its incentive policies and workload management to enhance the motivation and satisfaction of its healthcare workers. Further studies with additional variables and more diverse methodologies are recommended to deepen the understanding of factors affecting job satisfaction in this sector.